Integrated micro/nano drug delivery system based on magnetically responsive phase-change droplets for ultrasound theranostics - Chen, Jieying; Zhao, Chan; Liu, Hao; Wang, Zhangchao; Ma, Luyao; Zhang, Jiamin; Xu, Ning; Hu, Ke; Duan, Lei (Frontiers in Bioengineering and Biotechnology, 2024)
Phase-change droplets (PCDs) are intelligent responsive micro and nanomaterials developed based on micro/nano bubbles. Subject to external energy inputs such as temperature and ultrasound, the core substance, perfluorocarbon (PFC), undergoes a phase transition from liquid to gas. This transformation precipitates alterations in the PCDs' structure, size, ultrasound imaging capabilities, drug delivery efficiency, and other pertinent characteristics. This gives them the ability to exhibit "intelligent responses". This study utilized lipids as the membrane shell material and perfluorohexane (PFH) as the core to prepare lipid phase-change droplets. Superparamagnetic nanoparticles (PEG-functionalized Fe3O4 nanoparticles) and the anti-tumor drug curcumin (Cur) were loaded into the membrane shell, forming magnetic drug-loaded phase-change droplets (Fe-Cur-NDs). These nanoscale phase-change droplets exhibited excellent magnetic resonance/ultrasound imaging capabilities and thermal/ultrasound-mediated drug release. The Fe-Cur-NDs showed excellent anti-tumor efficacy for the MCF-7 cells under low-intensity focused ultrasound (LIFU) guidance in vitro. Therefore, Fe-Cur-NDs represent a promising smart responsive theranostic integrated micro/nano drug delivery system.